Emergence of rare and uncommon yeast-like pathogens causing neonatal sepsis at a tertiary care center, North India - Rai A.K.; Tilak R.; Tiwari P.; Meena P.; Kumar A.; Tiwari A.K.; Gupta M.K. (My University, 2025)
Introduction Neonatal candidemia is a life-threatening event in babies requiring ICU admission. Prompt diagnosis and appropriate treatment reduce mortality and morbidity. Worldwide, there is an emergence of drug-resistant rare Candida species causing neonatal sepsis that necessitates antifungal susceptibility testing in each case. Methods We did a prospective study to isolate Candida species causing neonatal sepsis and to determine the predisposing risk factors and time to positivity for flagged positivity. We also determined fluconazole, itraconazole and amphotericin B minimum inhibitory concentration (MIC) against isolated Candida species by broth microdilution method using CLSI M27-A3 guidelines. Results A total of 107 neonatal candidemia events were noted. Prematurity was the most common predisposing risk factor. Most isolates were non-albicans Candida. Candida utilis, C. pelliculosa, C. tropicalis and K. ohmeri were the predominant fungi causing neonatal candidemia. A varied antifungal MIC against isolated Candida species was noted. However, 90% of the isolated Candida strains had <8 µg/mL fluconazole MIC. Moreover, ≥8 and ≥2 µg/mL MIC for fluconazole and amphotericin B respectively were also noted. Conclusions Rare Candida species having varied fluconazole and amphotericin B MIC cause neonatal candidemia. Therefore, culture isolation and antifungal susceptibility testing should be done in each case of neonatal candidemia. © GERMS 2024.